The economic effects of refugee return - Uri Dadush (Kiel Institute for the World Economy (IfW), 2018)
The recent surge in the number of forcibly displaced persons who cross international borders in search of protection has prompted interest in evaluating policies that achieve the possible "end points" of the phenomenon. As envisaged by the United Nations High Commissioner for Refugees (UNHCR), these are the integration of the forcibly displaced persons in the country of destination, relocation in a third country, and return to the country of origin. The focus of this brief is on the third aspect, namely the appropriate conduct of return policy viewed from the perspective of the host country and, although the vast majority of forcibly displaced people are found in developing countries, the object here are policies in advanced countries.
Keywords: F22; F66; J61; 330; refugees; return; migration; integration; displacement; forced; repatriation; deportation